2007
DOI: 10.1142/s0218127407018245
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinth Chaos

Abstract: A particularly simple and mathematically elegant example of chaos in a three-dimensional flow is examined in detail. It has the property of cyclic symmetry with respect to interchange of the three orthogonal axes, a single bifurcation parameter that governs the damping and the attractor dimension over most of the range 2 to 3 (as well as 0 and 1) and whose limiting value b = 0 gives Hamiltonian chaos, three-dimensional deterministic fractional Brownian motion, and an interesting symbolic dynamic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…We observed that the other expressions which only involved the terms +, -, ×, ÷, without the sine term, were mostly variants of the Lorenz system with almost similar time domain dynamics. After screening with the evolved attractors with LLE > 0.1 in the time delay embedding technique, their true LLE was again computed directly from the structure of the differential equations using symbolic differentiation and are reported in Table 1 -4. There are a few research results on the increase in the number of equilibrium points in the phase space due to the sine terms which is commonly known as the 'Labyrinth chaos' [31], [32]. Similar complex dynamics have also been observed in the phase space due to increase in the number of equilibrium points beside the standard two wing Lorenz like attractor dynamics.…”
Section: Discussionmentioning
confidence: 95%
“…We observed that the other expressions which only involved the terms +, -, ×, ÷, without the sine term, were mostly variants of the Lorenz system with almost similar time domain dynamics. After screening with the evolved attractors with LLE > 0.1 in the time delay embedding technique, their true LLE was again computed directly from the structure of the differential equations using symbolic differentiation and are reported in Table 1 -4. There are a few research results on the increase in the number of equilibrium points in the phase space due to the sine terms which is commonly known as the 'Labyrinth chaos' [31], [32]. Similar complex dynamics have also been observed in the phase space due to increase in the number of equilibrium points beside the standard two wing Lorenz like attractor dynamics.…”
Section: Discussionmentioning
confidence: 95%
“…A very detailed study of this system was undertaken in [16] and it is presented as a prototypical example of chaos in [17]. As it is noted in [16], "Despite its mathematical simplicity, this system of ordinary differential equations produces a surprisingly rich dynamic behaviour that can serve as a prototype for chaos studies". They also remark that in the case of chaotic walks, the approach of an ensemble of initial conditions to equilibrium is by way of fractional Brownian motion with a Hurst exponent of approximately 0.61 and a slightly leptokurtic distribution.…”
Section: Labyrinth Chaos and Hyperchaosmentioning
confidence: 99%
“…In fact, the number of subsystems is not limited to two and the subsystems are not necessary to be identical in system parameters and even in dimension. Labyrinth chaos [Thomas, 1999;Sprott & Chlouverakis, 2007] is a good example, including three identical linear subsystems entangled by sine function. Here, we entangle three linear subsystems with different parameters and different dimensions.…”
Section: Chaos Entanglement With Different Subsystemsmentioning
confidence: 99%